ISLAMIC CULTURE AND MEDICINE (International Journal of Food and Nutritional Sciences, 2023)
The Prophet and his way of life, his Sunnah, which is then transmitted through the ummah in a variety of manifestations, are the embodiment of the metaphysics and ethics of the Quran in Islam. The dimension of Islamic culture is an extension of the Sunnah, which is a spontaneous creative activity of souls given life and nourishment by a revelation and way of life. "Quranized" souls creating what they consider to be beautiful and harmonious and prolonging the truth of the Quran in stone, ink, cloth, and rhyme. Islam made it possible for oneness to manifest in multiplicity, resulting in harmony and beauty in forms. All beauty has an intelligibility that communicates something of the creator's point of view. Islamic medicine provides a spiritual healing practice to lead a healthy and peaceful life.